GLOBAL DIPLOMACY INDEX AS A BASIS FOR THE CONCEPTUAL DESIGN OF THE FUTURE MODEL OF ECONOMIC INTERACTION AND INTEGRATION OF COUNTRIES - Liutak, Olena; Baula, Olena (Current Problems of Sustainable Development, 2026)
The article examines the role of the Global Diplomacy Index as a fundamental element of the conceptual design of an offensive model of economic interaction and integration of countries in the context of the transformation of the global economic system. It is substantiated that under conditions of intensified geoeconomic competition, fragmentation of global markets, digitalization of international relations, and  transformation of global value chains, the diplomatic infrastructure of a state acquires strategic importance as an instrument for ensuring economic interests. It is determined that the Global Diplomacy Index is an integrated indicator of a country’s international presence, characterizing the scale of diplomatic networks, the level of institutional interaction, and the potential of geoeconomic influence. The main approaches to assessing diplomatic activity and modern trends in the development of economic diplomacy are analyzed. It is established that countries with extensive diplomatic networks have greater potential for integration into international markets, attracting investments, developing trade and economic cooperation, and forming strategic partnerships. Particular attention is paid to the activities of the Lowy Institute and the peculiarities of the formation of the Global Diplomacy Index as an international analytical tool for assessing diplomatic presence. It is proved that the offensive model of economic interaction involves the active use of diplomatic, economic, and institutional mechanisms to expand a country’s international economic presence. The expediency of using the Global Diplomacy Index as a strategic guideline in the formation of the state’s foreign economic policy is substantiated. The prospects for using Ukraine’s diplomatic potential in the processes of European integration, post-war recovery, and diversification of international economic relations are identified.
Keywords: global diplomacy; economic diplomacy; international economic relations; integration of countries; geoeconomic competition; diplomatic network; foreign economic policy; Global Diplomacy Index; international interaction; economic integration